Culture, agency and power: Theoretical reflections on informal economic networks and political process - Kate Meagher (Danish Institute for International Studies (DIIS), 2009)
Do network theory really offer a suitable concept for the theorization of informal processes of economic regulation and institutional change? This working paper challenges both essentialist and skeptical attitudes to networks through an examination of the positive and negative effects of network governance in contemporary societies in a range of regional contexts. The analysis focuses on three broad principles of non-state organization - culture, agency and power - and their role in shaping processes of economic and political governance. It will be shown that the effective theorization of informal regulatory processes requires attention to the specific interaction of culture, agency and power in particular social contexts. Emphasizing a grounded theory approach, this article draws on cutting-edge network research from East Asia, Eastern Europe, Africa and Western societies to develop theoretical tools for the comparative study of non-state governance and its impact on wider processes of institutional change.
Keywords: 330; Soziales Netzwerk; Grounded Theory; Institutioneller Wandel; Welt